The global burden of non-conflict related firearm mortality. Issue 6 (2nd December 2005) - Richmond, T S; Cheney, R; Schwab, C W
Abstract : Objective: Understanding global firearm mortality is hindered by data availability, quality, and comparability. This study assesses the adequacy of publicly available data, examines populations for whom firearm mortality data are not publicly available, and estimates the global burden of non-conflict related firearm mortality. Design: The design is a secondary analysis of existing data. A dataset of countries, populations, economic development, and geographic regions was created, using United Nations 2000 world population data and World Bank classifications of economic development and global regions. Firearm mortality data were obtained from governmental vital statistics reported by the World Health Organization and published survey data. A qualitative review of literature informed estimates for the 15 most populous countries without firearm death data. For countries without data, estimates of firearm deaths were made using quartiles of observed rates and peer reviewed literature. Main outcome measures: Non-conflict related firearm deaths. Results: Global non-conflict related firearm deaths were estimated to fall between 196 000 and 229 000, adjusted to the year 2000. 162 800 firearm deaths adjusted for the year 2000 came from countries reporting data and represent 35% of the world's 186 countries. Public data are not available for 122 of these 186 countries, representing more than three billion (54%) of the world's population, predominately in lower and lower middle income countries. Estimates of firearm death for those countries without data range from 33 200 to 66 200. Conclusions: This study provides evidence that the burden of firearm related mortality poses a substantial threat to local and global health.